CARANGMAS MAKING MACHINE DESIGN USING THE ERGONOMIC APPROACH (CASE STUDY ON MICRO SMALL MEDIUM ENTERPRISES (MSME)) - Yoga Putra Alviansyah; Widhy Wahyani (Journal of Innovation Research and Knowledge, 2024)
Ms. Tuminah's Carangmas MSME is a Carangmas home industry located in Sidorahayu Village, Wagir District, Malang Regency. Ms. Tuminah's Carangmas MSME produces Carangmas. MSME Carangmas Mrs. Tuminah was established in 2019, to date employs 4 employees. Where the process of making carangmas is still manual and requires a long time during the process. To fulfill an order of 1500-5000 carangmas in one order, it takes up to 3 (three) days in the manufacturing process. Because at this time the MSMEs are still using simple tools, the time needed for the production process is still fairly long. Moreover, there is still the possibility of work accidents in some of the manufacturing processes. The methodology for designing the Crangmas Making Machine begins by surveying the field to observe the production process, collecting and processing working time data to be used as a support to analyze the time, size, and position of body movements, which are carried out by workers in carrying out work activities with old tools., collecting and processing work data with old conditions, designing Carngmas Manufacturing Machines. The data sources used are primary data and secondary data. The data used in assisting the design of the Carangmas Making Machine include qualitative data (interviews), and anthropometric data. From the results of the design of the workings of the carangmas making machine, namely an electric motor with a speed of 1200 rpm as the driving force for the Mixing and Printing tool. Mixing and printing system. The working system of this tool is the motor connected to the main pulley with a V-belt. the Pulley is a transmitted to the stirrer so that the process of the tool can work together with each other. From the results of using the new machine, the standard time calculation is 0.84 kg/minute if the old tool is 0.72 kg/minute so there is an increase in productivity when the increase is 12%.